Multiple environmental exposures in early-life and allergy-related outcomes in childhood. (November 2020) - Granum, Berit; Oftedal, Bente; Agier, Lydiane; Siroux, Valerie; Bird, Philippa; Casas, Maribel; Warembourg, Charline; Wright, John; Chatzi, Leda; de Castro, Montserrat; Donaire, David; Grazuleviciene, Regina; et al.
Highlights: Associations between early-life exposome and allergy-related outcomes were studied. No childhood exposures were associated with the allergy-related health outcomes. Prenatally, traffic variables, PMabs and phthalates were associated with rhinitis. Prenatally, traffic variables and phthalates were associated with itchy rash. Abstract: Introduction: Early onset and high prevalence of allergic diseases result in high individual and socio-economic burdens. Several studies provide evidence for possible effects of environmental factors on allergic diseases, but these are mainly single-exposure studies. The exposome provides a novel holistic approach by simultaneously studying a large set of exposures. The aim of the study was to evaluate the association between a broad range of prenatal and childhood environmental exposures and allergy-related outcomes in children. Material and Methods: Analyses of associations between 90 prenatal and 107 childhood exposures and allergy-related outcomes (last 12 months: rhinitis and itchy rash; ever: doctor-diagnosed eczema and food allergy) in 6–11 years old children (n = 1270) from the European Human Early-Life Exposome cohort were performed. Initially, we used an exposome-wide association study (ExWAS) considering the exposures independently, followed by a deletion-substitution-addition selection (DSA) algorithm considering all exposures simultaneously. All the exposure variables selected in the DSA were included in a final multi-exposure model using binomial general linear model (GLM). Results: In ExWAS, no exposures were associated with the outcomes after correction for multiple comparison. In multi-exposure models for prenatal exposures, lower distance of residence to nearest road and higher di- iso -nonyl phthalate level were associated with increased risk of rhinitis, and particulate matter absorbance (PMabs ) was associated with a decreased risk. Furthermore, traffic density on nearest road was associated with increased risk of itchy rash and diethyl phthalate with a reduced risk. DSA selected no associations of childhood exposures, or between prenatal exposures and eczema or food allergy. Discussion: This first comprehensive and systematic analysis of many environmental exposures suggests that prenatal exposure to traffic-related variables, PMabs and phthalates are associated with rhinitis and itchy rash.